Peramalan Inflasi di Indonesia Pasca Pemilu 2024 dengan Metode Time Series Double Exponential Smoothing - Anwar, Khoirul; Iryanto, Rivaldo Kurniawan; Harahap, Rifqah; Sinuraya, Asmah; Munizu, Musran (Jurnal EMT KITA, 2025)
Inflation is an increase in the prices of goods and services in a certain period whose growth is sought to remain low and stable for the sake of society's welfare. The aim of this research is to predict or predict the rate of inflation which will contribute to Indonesia economic uncertainty after the 2024 General Election. The data used in this research is secondary data obtained from the Bank Indonesia website. This research uses Indonesian monthly inflation data from 2015 to 2024. The data is analyzed using the Double Exponential Smoothing method. The results of the analysis showed that descriptive analysis of Indonesian inflation from 2015 fluctuated and continued to decline until in 2021 it reached 1.67% and increased in 2022 reaching 5.51% and continued to decline in the following year. Forecasting results using the Double Exponential Smoothing method continue to decline for December 2024 to April 2025 with a MAD error value of 0.3202. Inflation forecasting in Indonesia is expected to support interested parties in making policies to maintain country stability and control economic uncertainty after the election.